A Comprehensive Review of Functional Vision Loss. - Polacco, Amanda M.; Mozlin, Rochelle (Optometry & Visual Performance, 2021)
Background: Functional vision loss (FVL) is a broad term referring to loss of vision or visual field due to a non-organic etiology. This case report presents a comprehensive review of forms of FVL including etiology, presentation, clinical findings, and treatment options. In addition, it proposes how to thoroughly differentiate concomitant ocular disease. Case Report: A fourteen-year-old Caucasian female presented for evaluation of worsening blurred vision at all distances that started a few months prior to examination. There was minimal visual improvement through spectacle correction. Thorough ocular examination of the anterior and posterior segments yielded no ocular pathology to correlate to the reduction in vision. Baseline imaging of the optic nerve and macula were performed to ensure that anatomical structures were intact. Baseline visual fields revealed nonspecific scattered defects. Visual evoked potential (VEP) testing was normal and suggested intact neural pathways with vision of 20/20 in each eye. Bilateral visual loss in the presence of normal VEPs is confirmation of functional vision loss. Conclusions: Each condition classified under FVL overlaps in clinical presentation. Ultimately, it is crucial for clinicians to recognize FVL and provide patients with the referrals necessary.